O regionalismo no conto O Carro dos Milagres de Benedicto Monteiro - ALVES, Elis Regina Gonçalves (2023)
This paper aims at a study of the tale Car Benedicto dos Milagres Miller and the theoretical ground regionalism, it being understood that this literary trend is seen as a minor literature within the most famous Brazilian literature circles. To this end, we sought a reference to this support and guarantee the legitimacy of regionalism as a form of fictional expression through a theorization which sought concepts, historicizing and philosophical currents that addressed the topic. From there, deepened the analysis of the theme within the tale, seeking parallels and comparisons between theoretical frameworks and narrative action devised by the author on the screen in an attempt to relativize the academic vision and vision emanating fictional tale.